What does integrated care look like in a perioperative service? - Jed Duff (Journal of Perioperative Nursing)
The traditional approach to planning care based on surgical procedures rather than patient needs is no longer fit for purpose. The typical surgical patient has grown increasingly more complex over the past decade due to a combination of clinical and social factors. If this complexity is poorly managed, it can result in substantial and avoidable increases in length of hospital stay, post-operative complications, hospital readmissions, delayed recovery and reduced quality of life.